Associations of Abdominal Obesity and New‐Onset Atrial Fibrillation in the General Population. Issue 6 (6th June 2017) - Baek, Yong‐Soo; Yang, Pil‐Sung; Kim, Tae‐Hoon; Uhm, Jae‐Sun; Park, Junbeom; Pak, Hui‐Nam; Lee, Moon‐Hyoung; Joung, Boyoung
Abstract : Background: Higher height and weight are known to be associated with higher risk of atrial fibrillation (AF); however, whether the risk of AF is related to abdominal obesity is unclear. Methods and Results: We studied 501 690 adults (mean age: 47.6±14.3 years; 250 664 women [50.0%]) without baseline AF in the National Sample Cohort released by the National Health Insurance Service in Korea. Body mass index (underweight defined as <18.5; normal, 18.5 to <25.0; overweight, 25.0 to <30.0; and obese, ≥30.0) and waist circumference (abdominal obesity defined as ≥90 cm for men and ≥80 cm for women) were evaluated. During a mean follow‐up of 3.9±1.3 years, 3443 participants (1432 women [41.6%]) developed AF. In multivariable models adjusted for clinical variables, the AF risk of underweight, overweight, and obese individuals increased by 21% (95% confidence interval, 1.01–1.45, P =0.043), 14% (95% confidence interval, 1.06–1.23, P <0.001), and 52% (95% confidence interval, 1.30–1.78, P <0.001), respectively, compared with those with normal body mass index. AF risk with confounder‐adjusted hazards for abdominal obesity was 18% (95% confidence interval, 1.10–1.27, P <0.001). The increased AF risk was present in abdominally obese individuals regardless of body mass index except for the obese group. In subgroup analysis, abdominal obesity by waist circumference conferred increased risk of new‐onset AF, particularly in participants without comorbidities. Conclusions: Abdominal obesity is an important, potentially modifiable risk factor for AF in nonobese Asian persons. These data suggest that interventions to decrease abdominal obesity may reduce the population burden of AF.